COMPARISON OF OPTICAL BIOMETRY AND A SCAN FOR CALCULATION OF INTRAOCULAR LENS POWER IN AGE RELATED NUCLEAR CATARACT AT TERTIARY CARE EYE HOSPITAL: Intraocular Lens Power - Rafique, Aisha; Zafar, Omar; Khan, Summaya (Pakistan Armed Forces Medical Journal, 2021)
Objective: To compare optical biometry and A-scan for calculating intraocular lens power in patients with nuclear cataract at tertiary care eye hospital. Study Design: Cross sectional comparative study. Place and Duration of Study: Armed Forces Institute of Ophthalmology, Pak Emirates Military Hospital, Rawalpindi, from Jul to Dec 2018. Methodology: In this study 70 eyes of 70 patients planned for cataract surgery by phacoemulsification underwent both optical biometry with intraocular lens master and ultrasound biometry applanation by A scan after informed consent. Intraocular lens power calculated by these two methods of biometry was compared. Phacoemulsification surgery was performed through a 2.3 mm superior temporal clear corneal incision. All patients underwent in the bag implantation of the same intraocular lens type. Results: The mean age of the patients was 62.89 ± 6.69 years. A significant (p-value<0.001) difference in intraocular lens power calculation was noted (20.96 ± 1.76 vs. 22.03 ± 1.61) with optical biometry and A-scan respectively. Association on the basis of age groups showed a significant (p-value<0.001) difference in both strata that was among patients having age ≤65 years and patients having age >65 years. Conclusion: Optical biometry was found efficient and safe method for calculation of intraocular lens power. Optical biometry is noncontact method having very less chance of infection and suitable for most of the eye types.